RETRACTED: Analysis of trends and forecasting of tuberculosis mortality at the regional level - Cherniaev Igor; Tsvetkov Andrey; Chugaev Yury; Chernavin Pavel (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001